Improving appropriateness of oxygen saturation monitoring in paediatric patients with acute respiratory illness: a QI initiative. (18th May 2018) - Parisien, Brigitte; Cheng, Daryl; Marano, Maria; Johnstone, Julie; Carmichael, Nicole; Al-Maawali, Ali; Gamulka, Beth
Abstract: BACKGROUND: Oxygen saturation monitoring (OSM) is a key aspect of clinical care in paediatric patients with acute respiratory disease. It is commonplace in the assessment of children with bronchiolitis, asthma and pneumonia and serves as a proxy for illness severity. However, there is a paucity of standardized guidelines around appropriate pulse oximetry and OSM use in these patients. Some preliminary evidence shows that intermittent pulse oximetry is as safe as continuous oximetry monitoring in children with bronchiolitis. Furthermore, inappropriate OSM may lead to overdiagnosis and overtreatment of mild hypoxia with no demonstrable clinical improvement and therefore contribute to prolonged length of stay. OBJECTIVES: As part of The Choosing Wisely campaign, our aim is to increase the appropriate use of OSM in paediatric inpatients with asthma, bronchiolitis or pneumonia in our center to 90% by April 2018. DESIGN/METHODS: Appropriate monitoring is defined as intermittent OSM when a patient is off oxygen for >2 hours and continuous OSM whilst the patient is receiving supplemental oxygen. A 4 week pre-intervention baseline chart review showed 62% (23/37) had appropriate OSM. Series of interventions along the hierarchy of effectiveness were then chosen to improve the main outcome measure: Educational sessions oriented at medical and nursing staff were provided to guide evidence-based practice and to reinforce the use of specific orders around OSM; Visual cues were used in strategic locations to remind medical staff of appropriate OSM and to prompt discussion during ward rounds; Weekly reminders and performance updates were displayed and electronically circulated to medical and nursing staff. Post-intervention data collection occurred via convenience sampling by project leaders from December 2017 to April 2018. A PDSA cycle approach was used to modify interventions. RESULTS: OSM appropriateness increased to 78% (56/72) in the first 4 weeks post-initial interventions. There were no negative impacts on balancing measures. We anticipate an ongoing graded increase in appropriateness across the study period triggered by collective staff awareness and synergistic interventions. CONCLUSION: This QI initiative will improve the appropriate use of OSM in patients admitted for bronchiolitis, pneumonia or asthma at our paediatric tertiary hospital without increasing the number of patient safety events or admissions to the intensive care unit. Further interventions are planned to ensure greater uptake and sustainability.